2018
DOI: 10.5430/cns.v6n3p46
|View full text |Cite
|
Sign up to set email alerts
|

Social and healthcare staff’s self-reported simulation learning needs in small and middle-sized enterprises

Abstract: Objective: The study describes learning needs of social and healthcare staff in small and middle-sized enterprises, which participate in a simulation-based coaching project. The study aims at producing knowledge that can be used to develop the content of multiprofessional simulation-based coaching. Methods: Data were collected through an online survey using a questionnaire with quantitative and qualitative items. The qualitative data were analyzed using inductive content analysis and the statistical data using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Other learning needs involved the management of acute situations, coping with aggressive behaviour and the use of digital tools and information technology. The more detailed results have been described in articles published recently (Salminen-Tuomaala et al 2018, Salminen-Tuomaala et al 2019.…”
Section: Resultsmentioning
confidence: 96%
“…Other learning needs involved the management of acute situations, coping with aggressive behaviour and the use of digital tools and information technology. The more detailed results have been described in articles published recently (Salminen-Tuomaala et al 2018, Salminen-Tuomaala et al 2019.…”
Section: Resultsmentioning
confidence: 96%
“…Research has shown that continuous professional development is important and that learning in the work environment is useful from the perspective of individuals and organizations alike. [1,2] It has been proposed that not only concrete, situation and workplace-specific, but also adaptable, trans-ferable learning can take place in workplaces, either through everyday activities or through organized workplace learning. Transferable and conceptual learning is thus not only confined to educational institutions.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In the world of work, effective educational interventions are based on an assessment of learning needs, tailored to the needs of the organization and, if possible, carried out in the work context, in the organization's premises. [2,7] It has been suggested that besides attending to specific learning needs, the educators should look into the training culture, that is the meanings and values attributed to training in the organization. The individual, group, and organizational aspects of training culture may be different, and a clash may exist between employee and management perspectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many skills, such as interaction, collaboration and teamwork skills, may be best learnt through action-based methods. [23][24][25] Simulation pedagogy carried out with multiprofessional small groups can help participants understand each other's roles and responsibilities [26,27] and facilitate sharing good practices. At the heart of learning lies an evolving companionship, through which added value can be gained.…”
Section: Introductionmentioning
confidence: 99%